STUDY OF BRAND IMAGE, CREATIVE MARKETING IN MEDIATING PRODUCT QUALITY AND SERVICE QUALITY ON CONSUMER LOYALTY AT MCDONALD'S DKI JAKARTA AREA DURING THE COVID-19 PANDEMIC - Tj, Hery Winoto; Tecoalu, Melitina; Mannuela, Roseline; Widjaja, Daniel; Colline, Fredella; Wahyoedi, Soegeng (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Covid-19 pandemic period is quite a difficult time and has an impact on all sectors including the culinary sector. The times have made a shift in people's lifestyles, where people are now more likely to adopt an instant and fast-paced lifestyle. In terms of the culinary industry, this lifestyle shift has made more outlets from fast food restaurants. In order to remain competitive, fast food restaurants are required to continue to design marketing strategies to retain their customers and attract new consumers. This study aims to analyze the role of brand image and creative marketing in mediating product quality and service quality on customer loyalty at McDonald's outlets in the DKI Jakarta area during the Covid-19 pandemic. The sampling technique used is purposive sampling. The results show that brand image is a very important aspect in creating consumer loyalty, while creative marketing is not proven to have a role in mediating the relationship between product quality and service quality to customer loyalty without the role of brand image in it.